Development of Virtual Reality for Optical Fiber Splicing Simulation - Bahaduri, Rahmat Gah; Sindu, I Gede Partha; Wahyuni, Dessy Seri (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
This study aims to determine the design and evaluation of content and media experts in the development of Virtual Reality for Optical Fiber Splicing Simulation. The research method used is Research & Development with the Multimedia Development Life Cycle (MDLC) model which consists of concept, design, material collecting, assembly, testing, and distribution stages. This Virtual Reality development uses the Unity application in making applications with the Oculus Quest 2 device. The data collection process begins with interviews with educators about the learning that takes place, and the difficulties experienced. At the testing stage, Blackbox Test, Content Expert Test: 1.00 Validity Coefficient, and Media Expert Test: 1.00 Validity Coefficient. Virtual Reality for Fiber Optic Splicing Simulation offers simulation before implementing splicing in real. By taking characteristics of life such as laboratories, educators, and fiber optic practicum tools. Virtual reality can provide situations and conditions for students to practice Optical Fiber Splicing by entering a virtual laboratory in cyberspace. The learning experience in Virtual Reality that provides a sense of immersion in a virtual environment using Full Hand Interaction that applies the Hand Tracking function in Oculus Quest 2. Based on the overall test, the development of Virtual Reality for Optical Fiber Splicing Simulation is feasible to use and distribute to target students.